The role of ATF4 stabilization and autophagy in resistance of breast cancer cells treated with Bortezomib. - Milani, M; Rzymski, T; Mellor, H; Pike, L; Bottini, A; Generali, D; Harris, A (2009)
The ubiquitin-proteasome system plays a key regulatory role in cellular homeostasis. The inhibition of the 26S proteasome by Bortezomib leads to the accumulation of misfolded proteins, resulting in endoplasmic reticulum stress followed by a coordinated cellular response called unfolded protein response (UPR). Endoplasmic reticulum stress is also a potent inducer of macroautophagy. Bortezomib is a selective and potent inhibitor of the 26S proteasome and is approved for the treatment of multiple myeloma. Clinical trials with Bortezomib have shown promising results for some types of cancers, but not for some others, including those of the breast. In this study, we show that Bortezomib induces the UPR and autophagy in MCF7 breast cancer cells. Surprisingly, Bortezomib did not induce phosphorylation of PERK, a key initial step of the UPR. We show that induction of autophagy by Bortezomib is dependent on the proteasomal stabilisation of ATF4 and up-regulation of LC3B by ATF4. We show that ATF4 and LC3B play a critical role in activating autophagy and protecting cells from Bortezomib-induced cell death. Our experiments also reveal that HDAC6 knockdown results in decreased LC3B protein and reduced autophagy. Our work shows that the induction of autophagy through ATF4 may be an important resistance mechanism to Bortezomib treatment in breast cancer, and targeting autophagy may represent a novel approach to sensitize breast cancers to Bortezomib.